Factors associated with a positive shock index in the prehospital setting after major trauma - Tim Andrews; Joanna F. Dipnall; Belinda J. Gabbe; Ben Beck; Shelley Cox; Peter A. Cameron (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Bleeding and coagulopathy are the leading causes of potentially preventable death and multi-organ damage after injury. Trauma care in the prehospital setting focusses on three key tenets; identification, lifesaving interventions and transport. Existing prehospital trauma triage guidelines use a combination of physiological, and patterns of injury to identify potential major trauma, however these guidelines are not designed to identify potential shock. Methods We conducted a registry-based cohort study using data from the Victorian State Trauma Registry (VSTR) on adult major trauma patients (≥ 16 years) transported by EMS between 2010 and 2020, including patients within 70 km of Melbourne’s major trauma services. Data from VSTR were linked with the Victorian Ambulance Clinical Information System and operational records from Ambulance Victoria. The primary outcome was shock, defined by a shock index (SI) ≥ 0.9.Logistic regression models stratified by transport mode examined associations with shock. Descriptive statistics and tests of association were used, followed by multivariate logistic regression. Results Over this 10-year study, 16,265 patients were identified within 70 km of the major trauma services. 26% of the patients had a shock index ≥ 0.9, and the majority of these patients (88%) were transported by road ambulance. The majority of the patients in this study (69%) were injured within 30 km of the MTS. Females had an increased adjusted odds of shock (aOR = 2.19), as did patients who were entrapped (aOR = 1.23). Discussion This study identified that over a quarter of major trauma patients experienced shock during the prehospital phase, with most lacking access to advanced lifesaving interventions typically provided by MICA-flight paramedics. These findings underscore the importance of aligning prehospital care systems with patient needs to optimize trauma outcomes. Conclusion Over 25% of major trauma patients developed a shock index ≥ 0.9 within the prehospital phase of their care. Furthermore, 88% of the shocked patients did not have access to the most advanced prehospital life-saving interventions available within the state.